The methodology of dealing with problematic Hadith: a fundamental and applied studies منهجية التعامل مع مشكل الحديث : دراسة تأصيلية تطبيقية - Suleiman, Hassan; Eletrebi, Mohamed Fathy (IIUM Press, 2021)
ABSTRACT: The books of the sunnah are historical documents with reports from the wisest of whom the world has known. Defaming the sunnah by looking superficially at the isnāds and the mutūns -as being done by some advocates of modernity- is often not meant to refute a particular ḥadīth; rather, to denounce the entire sunnah and the rulings which are derived from it. This research revolves around the subject of mushkil al-ḥadīth, the difference between it and mukhtalif al-ḥadīth, and the correct methodology in addressing problematic ḥadīth texts. The authors adopted the inductive- analytical approach in collecting indicants and extrapolating their imperatives. The research reached several conclusions: a mushkil is an ambiguous state that can only be resolved through extensive contemplation and consideration; a mushkil is relative, so what is ambiguous to a person may be clear to others; and a mushkil may be resolved through reconciliation, preference, abrogation and some other legitimate approaches of dealing with religious texts.